A movência das fronteiras: o ensaísmo nas crônicas de Clarice Lispector - Gomes, Cristina Torres (2008)
This research analyses the development of Clarice Lispector s columns for the newspaper Jornal do Brasil, written between 1967 and 1973. It considers the author s relations with Montaigne s constructive method about essays. It is important to make it clear that, in our investigative way, essays and chronicles are not seen as similar genres. What brings them close to each other is the way they fluently work with the language, right in the limit between the poeticism and the reflexive-philosophical area. Such hypothesis is based on two main points of confluence linking these two literary genres: the responsibility for the written way; and the invention of an I . To guide our research s purposes, we use two lines of theoretical grounds. The first line thinks about the narrator s voice and the sight development based on the studies of Walter Benjamin about the narrator and the flâneur. The second one thinks about the construction of the essayistic method and the creation of a chronicle s I , using Montaigne s Essays. To a corpus selection, we choose eight Clarice Lispector s chronicles published by Jornal do Brasil. Five of these were analyzed in this research based mainly in the theoretical ground, once they have the strength of a self and deep thought, establishing direct connections with the reflexive act about the creation of the chronicles author s I . The remaining chronicles, found in Chapter three, do not dialogue directly with the self-reflexive and self-critic voices, but with the writing in the text s background, what justifies our choose of deep analyzing the writing process, not only through the self-criticism, but also through the written structure of its composition. We conclude that Clarice Lispector s chronicles do have an essayistic composition method which can be seen in her entire literary creation: the consciousness of writing and the developing of a moving I , whose place is never established in the present time